2009
DOI: 10.1097/01.aids.0000363780.42956.ff
|View full text |Cite
|
Sign up to set email alerts
|

Linking family planning with HIV/AIDS interventions: a systematic review of the evidence

Abstract: Interventions linking family planning and HIV services were generally considered feasible and effective, though overall evaluation rigor was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 16 publications
6
90
0
Order By: Relevance
“…Our findings are consistent with the evidence base on facility-based FP/HIV African Journal of Reproductive Health June 2017; 21 (2): 79 integration models, which shows that linkages between FP and HTC can facilitate HTC uptake 3,21 , and also indicates improvements in contraceptive use through various combinations of FP and HIV services 3,4 . Although somewhat limited, the available literature does not provide evidence of negative effects from potentially increased staff time with clients as a result of integrating services, and effects on the quality of FP counseling when adding HTC are reported as positive or mixed 3,21 . The challenges we observed with the delivery of integrated messages echo process evaluation data from several studies on facility-based integration of FP into HIV services, which showed that provision of contraceptive counseling, while improved, was not systematic and was in some cases lower than expected 4 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings are consistent with the evidence base on facility-based FP/HIV African Journal of Reproductive Health June 2017; 21 (2): 79 integration models, which shows that linkages between FP and HTC can facilitate HTC uptake 3,21 , and also indicates improvements in contraceptive use through various combinations of FP and HIV services 3,4 . Although somewhat limited, the available literature does not provide evidence of negative effects from potentially increased staff time with clients as a result of integrating services, and effects on the quality of FP counseling when adding HTC are reported as positive or mixed 3,21 . The challenges we observed with the delivery of integrated messages echo process evaluation data from several studies on facility-based integration of FP into HIV services, which showed that provision of contraceptive counseling, while improved, was not systematic and was in some cases lower than expected 4 .…”
Section: Discussionsupporting
confidence: 88%
“…Research and programmatic experience have shown that integrated FP/HIV service delivery is a worthwhile strategy to comprehensively address clients' sexual and reproductive health needs [3][4][5] . This is especially the case in settings with high unmet need for FP and high HIV prevalence, like subSaharan Africa 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential benefits of integrating these services have been previously described and include increasing uptake of health services and prevention of unintended pregnancies, STIs including HIV, as well as of mother-to-child transmission of HIV and infant abandonment among HIV-infected females. 40,41 A recent review of programs linking family planning and HIV services found that integration was generally feasible and effective. 40 For street youth in Ukraine, community-based programs utilizing skilled outreach workers are critical to successfully reach and serve this high-risk and transient youth population.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 A recent review of programs linking family planning and HIV services found that integration was generally feasible and effective. 40 For street youth in Ukraine, community-based programs utilizing skilled outreach workers are critical to successfully reach and serve this high-risk and transient youth population. Fortunately, there are several existing evidence-based HIV prevention programs for homeless youth 42,43 that could be easily adapted to integrate pregnancy prevention, as most already aim to reduce HIV-related sexual behaviors (e.g., reduction of multiple sex partners or unprotected sex) that also reduce pregnancy risk.…”
Section: Discussionmentioning
confidence: 99%